Experimental and numerical study of the evolution of soot primary particles in a diffusion flame - Botero, Maria L. (2019)
The evolution of primary soot particles is studied experimentally and numerically along the centreline of a co-flow laminar diffusion flame. Soot samples from a flame fueled with C2H4 are taken thermophoretically at different heights above the burner (HAB), their size and nano-structure are analysed through TEM.